STRATEGI MENGHIDUPKAN MOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 - Irasma; Putri Maharani, Winarni; Fahira, Winda (Riau Education Journal, 2021)
The COVID-19 pandemic has had a significant impact on various sectors of life, especially in the field of education. During this pandemic, there have been several changes in the learning process and this has become a challenge for all educational institutions. Motivation has an important role in improving the quality of student learning, for that researchers are interested in examining the strategies used by SDN 02 Artificial I teachers in activating students' learning motivation during the COVID-19 pandemic. The data collection technique used by the researcher is an interview technique with a qualitative descriptive approach. The results showed that the form of the teacher's strategy to revive student learning motivation in the Study From Home (SFH) policy in the midst of the COVID-19 pandemic was by giving students' dream cards. This is proven to be able to turn on the learning motivation of SDN 02 Artificial I students.